2004
DOI: 10.1111/j.1365-2125.2003.02053.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quinidine, used as a probe for the involvement of P‐glycoprotein, on the intestinal absorption and pharmacodynamics of methadone

Abstract: AimsThere is considerable unexplained interindividual variability in the methadone doseeffect relationship. The efflux pump P-glycoprotein (P-gp) regulates brain access and intestinal absorption of many drugs. Evidence suggests that methadone is a P-gp substrate in vitro , and P-gp affects methadone analgesia in animals. However the role of P-gp in human methadone disposition and pharmacodynamics is unknown. This investigation tested the hypothesis that the intestinal absorption and pharmacodynamics of oral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
4
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 57 publications
4
72
4
2
Order By: Relevance
“…The plasma concentrations of the concomitant drugs in humans were obtained or assumed on the basis of the previous report (Jamis-Dow et al, 1997;Stewart et al, 2000;Kharasch et al, 2004;Brunton et al, 2005 ] values of quinidine (600 mg/man) after oral administration was 1.17, where the respiratory depressant effects of loperamide were observed. Of note, the dosage of quinidine in this study was relatively higher than the conventional therapeutic dosage (Brunton et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The plasma concentrations of the concomitant drugs in humans were obtained or assumed on the basis of the previous report (Jamis-Dow et al, 1997;Stewart et al, 2000;Kharasch et al, 2004;Brunton et al, 2005 ] values of quinidine (600 mg/man) after oral administration was 1.17, where the respiratory depressant effects of loperamide were observed. Of note, the dosage of quinidine in this study was relatively higher than the conventional therapeutic dosage (Brunton et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Coadministration of these inhibitors may result in the alteration of the pharmacokinetics of other drugs that are P-gp substrates (Kharasch et al, 2004;Nakagami et al, 2005). Recent studies have demonstrated that RSP increased the intracellular accumulation of P-gp substrates rhodamine123 (Rh123) and calcein-AM in bovine brain microvessel endothelial cells and MDR1 gene transfected MDCK cells, respectively, indicating that RSP is a potential P-gp inhibitor (Mahar Doan et al, 2002;Bachmeier and Miller, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several opioids have been reported previously in animals and/or humans to be in vitro or in vivo substrates for P-glycoprotein, including loperamide (Wandel et al, 2002;Skarke et al, 2003), morphine (Xie et al, 1999;Wandel et al, 2002;Dagenais et al, 2004), methadone (Dagenais et al, 2004;Kharasch et al, 2004), fentanyl (Wandel et al, 2002;Dagenais et al, 2004), alfentanil (Wandel et al, 2002;Kalvass et al, 2007), and sufentanil (Wandel et al, 2002). Norbuprenorphine has been identified as a substrate for P-gp-mediated efflux by in vitro screening using transfected Madin-Darby canine kidney (MDCK) cells (Tournier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%